Use of the PFA-100™ Apparatus to Assess Platelet Function in Patients Undergoing PTCA during and after Infusion of cE3 Fab in the Presence of other Antiplatelet Agents - Hézard, Nathalie; Metz, Damien; Nazeyrollas, Pierre; Droulle, Chantal; Elaerts, Jacques; Potron, Gérard; Nguyen, Philippe (Thrombosis and Haemostasis, 2000)
The PFA-100™ (Dade) is a new functional whole blood analyzer, the accuracy and reliability of which have been evaluated in von Willebrand disease and during acetyl salicylate acid therapy. This new test has the advantages of rapidity and simplicity. It may be useful to monitor new antiplatelet agents, such as GPIIb/IIIa receptor antagonists. The objective of this study was to assess the PFA-100™ in comparison with aggregometry and with the percentage of blockaded receptors GPIIb/IIIa during and after c7E3 Fab infusion in fifteen patients undergoing PTCA. Our results showed a change of closure time values from normal to abnormal within a small margin of flow cytometric values (60–75% of blockaded receptors), and moreover a variable platelet response to long-term low dose aspirin treatment in agreement with aggregometry. No influence with heparin was observed. In conclusion, this study shows that PFA-100™ may be helpful in the decision making for additional antiaggregant therapy before PTCA or in monitoring long-term GPIIb/IIIa receptor antagonist treatment.
Keywords: c7E3 Fab; acetyl salicylate acid; PFA-100™; platelet; monitoring